Investigation of corrosion and wear resistance of steels nitrided in a glow discharge in distilled water - Rudyk, O.Yu.; Kaplun, P.V.; Golenko, K.E.; Honchar, V.A.; Poberezhnyi, M.M. (Problems of Tribology, 2022)
The article is devoted to the study of corrosion resistance and wear resistance (sliding friction) of unhardened and glow discharge nitrided (ion or ion-plasma nitriding) structural steels 20, 45, 45X and 38X2МЮА in distilled water. The influence of temperature (T = 793 – 873 K), the composition of the saturating mixture (nitrogen N2, argon Ar and propane C3H8) and its pressure (Р = 80 – 450 Pa), the duration of the process on the structure and phase composition of the nitrided layers was studied (carried out using metallographic and X-ray structural analyses). A comparison of the physical and mechanical characteristics of the surface layer of unhardened and nitrided steels before and after the tests was carried out and it was concluded that nitrided steels have an increased service life due to greater hardness, corrosion resistance and wear resistance. It is recommended to increase the corrosion resistance of the studied steels in distilled water, to carry out their ionic nitriding in a nitrogen-containing atmosphere, and to increase wear resistance - in a carbon-containing atmosphere (carbonitriding).